Sejarah Perkembangan Filsafat dan Sains pada Zaman Yunani - Jarkasih Harahap, Ibnu Alwi; Salminawati; Ade Ilfah; Ummi Nadrah Nasution (Intitut Agama Islam Nasional Laa Roiba Bogor, 2024)
Ancient Greece was an important milestone in the history of the development of philosophy and science. This article will summarize the historical development of these two fields in Greece. In the 6th to 4th centuries BC, an intellectual culture grew in Greece known as the Classical Age. This research uses a library approach (library research). According to Mushtofa et al. (2020) bibliography research is research carried out in order to obtain information data obtained from various written sources. This research shows that the development of science in Ancient Greece and beyond was driven by the spirit of understanding the philosophy of humanism. The philosophy of humanism teaches that humans have the ability to regulate themselves and the universe around them. This belief has been present since ancient Greece and has been one of the main factors in the evolution of human thinking about nature.